2011
DOI: 10.4335/9.2.103-122(2011)
|View full text |Cite
|
Sign up to set email alerts
|

Foundation or Fragment of Local Democracy? Empirically Assessing the Roles of Local Councillors in Belgian Governance

Abstract: It is often argued that local governance conflicts with the prescribed functioning of local councillors. We could wonder if councillors have become fragments of local democracy, rather than the foundation they are supposed to be. This article empirically assesses the classic role-set (representation, policy, control) of local councillors in Belgian governance. Besides pointing to a gap between theory and practice, it underlines a substantial discrepancy between councillors’ role attitude and subsequent behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…9 Yet whilst the system of personal monism was intended to preserve council primacy, reality seems to work the other way around. Research has revealed that non-executive councillors are often marginalised in practice due to the dominance of a strong executive (Verhelst et al 2011).…”
Section: Research Question Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…9 Yet whilst the system of personal monism was intended to preserve council primacy, reality seems to work the other way around. Research has revealed that non-executive councillors are often marginalised in practice due to the dominance of a strong executive (Verhelst et al 2011).…”
Section: Research Question Methods and Datamentioning
confidence: 99%
“…This party dominance continues during councillors' careers as well and confirms Belgium as a typical party government. Accordingly, party politics partly explains why councillors from the opposition often fail to fulfil their designated role as representative, policy-maker and scrutiniser (Verhelst et al 2011).…”
Section: Research Question Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation